2023
DOI: 10.3389/fmolb.2023.1120373
|View full text |Cite
|
Sign up to set email alerts
|

Smith-Lemli-Opitz syndrome: A pathophysiological manifestation of the Bloch hypothesis

Abstract: The biosynthesis of cholesterol, an essential component of higher eukaryotic membranes, was worked out by Konrad Bloch (and Feodor Lynen) in the 1960s and they received the Nobel Prize around that time in recognition of their pioneering contributions. An elegant consequence of this was a hypothesis proposed by Konrad Bloch (the Bloch hypothesis) which suggests that each subsequent intermediate in the cholesterol biosynthesis pathway is superior in supporting membrane function in higher eukaryotes relative to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 197 publications
0
1
0
Order By: Relevance
“…Importantly, these results demonstrate that whereas actin polymerization acts as a negative regulator of cAMP signaling, cholesterol could act as a positive modulator. We believe that such dynamic reorganization of the actin cytoskeleton could represent an important determinant for membrane protein signaling in metabolic disorders such as Smith-Lemli-Opitz syndrome (SLOS) 90 that are due to defects in cholesterol biosynthesis pathways. It is worthwhile mentioning here that although it has been earlier reported that statins could inhibit GPCR signaling, 91 reorganization of actin cytoskeleton has never been proposed as an underlying mechanism.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Importantly, these results demonstrate that whereas actin polymerization acts as a negative regulator of cAMP signaling, cholesterol could act as a positive modulator. We believe that such dynamic reorganization of the actin cytoskeleton could represent an important determinant for membrane protein signaling in metabolic disorders such as Smith-Lemli-Opitz syndrome (SLOS) 90 that are due to defects in cholesterol biosynthesis pathways. It is worthwhile mentioning here that although it has been earlier reported that statins could inhibit GPCR signaling, 91 reorganization of actin cytoskeleton has never been proposed as an underlying mechanism.…”
Section: ■ Discussionmentioning
confidence: 99%